Opercularella lacerata - Calder, Dale R. (Zenodo, 2012)
Opercularella lacerata (Johnston, 1847) Fig. 23 Campanularia lacerata Johnston, 1847: 111, pl. 28, fig. 3. Opercularella lacerata .— Segerstedt, 1889: 14, 25.— Lönnberg, 1898: 52.— Jäderholm, 1909: 81, pl. 7, fig. 13. Campanulina lacerata .— Jägerskiöld, 1971: 61. Type locality. UK: Berwick Bay; St. Andrews (Johnston 1847: 111). Museum material. Tjärnö, floating dock at Sven Lovén Centre for Marine Sciences, 58°52’33.68”N, 11°08’43.65”E, <1 m, 07.ix.2010, collected manually, on a fucoid alga, one colony, up to 3.5 mm high, without gonophores, ROMIZ B3890. Remarks. Opercularella lacerata (Johnston, 1847) is frequent on floating docks just beneath the surface of the water on both sides of the boreal North Atlantic (personal observations), and it was found in that environment at Tjärnö. It is a euryhaline species, extending deep into the Baltic Sea (Cornelius 1995a). The boreal Opercularella pumila Clark, 1875 is somewhat similar, but its colonies are at least partly stolonal. Erect colonies of that species are more compact than those of O. lacerata and seldom have more than a half-dozen hydranths and hydrothecae per stem. Although gonophores are fixed sporosacs in both, gonothecae of O. lacerata are oval to subcylindrical while those of O. pumila are fusiform with a tapered neck (Clark 1875; Calder 1971). Also similar is Phialella quadrata (Forbes, 1848), but it differs from O. lacerata in having a medusa stage rather than fixed sporosacs. Schuchert (2001b) noted that trophosomes of O. lacerata can be distinguished from P. quadrata in having: (1) larger hydrothecae (0.3–0.5 mm vs. 0.25 mm), and (2) pedicels that are usually shorter (with five rings or less) instead of as long or longer (with more than five rings) than the hydrothecae. Other characters useful in distinguishing the two were presented by Cornelius (1995a: 176). The hydroid of Phialella quadrata has not yet been reported from southwestern Scandinavia; the report by Cornelius (1995a) that Kramp (1935b) and Rees & Rowe (1969) had recorded it from Denmark and Sweden is in error. It was included by Kramp (as Campanulina minuta Stechow, 1923) as a species that might be expected to occur in Danish waters, but its known distribution was stated to be the Orkney Islands and possibly Kiel. Rees & Rowe made no mention of P. quadrata in their report. In southwestern Scandinavia, colonies of O. lacerata were found throughout the year in the Oslofjord by Christiansen (1972), although gonophores were observed only during May and June. It is common on the Danish coast (Kramp 1935b) and is likely much more abundant and ubiquitous in waters of western Sweden than records presently indicate. Information on the biology of the species was summarized by Cornelius (1995a). Reported distribution. West coast of Sweden.—Tjärnö (this study) to Kungsbackafjorden (Jägerskiöld 1971). Elsewhere.—North Atlantic from Svalbard (Ronowicz 2007) and the White Sea to the Mediterranean (Cornelius 1995a) in the east, and from Greenland (Schuchert 2001a) and Foxe Basin in the Canadian north (Calder 1970) to Long Island Sound (Fraser 1944) in the west. FIGURE 24. Racemoramus panicula : part of hydrocaulus with two branches and hydrothecae, ROMIZ B3916. Scale equals 0.5 mm. : Published as part of Calder, Dale R., 2012, On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region 3171, pp. 1-77 in Zootaxa 3171 (1) on pages 23-24, DOI: 10.11646/zootaxa.3171.1.1, http://zenodo.org/record/5247704 : {"references": ["Johnston, G. (1847) A history of the British zoophytes. Second edition. John Van Voorst, London, 488 pp.", "Segerstedt, M. (1889) Bidrag till kannedomen om hydroid-faunan vid Sveriges vestkust. Bihang till Kongliga Svenska Vetenskaps-Akademiens Handlingar, 14, Afdelning 4, 4, 1 - 28.", "Lonnberg, E. (1898) Undersokningar rorande Oresunds djurlif. Meddelanden fran Kongl. Landtbruksstyrelsen, ar 1898, 43, 1 - 77.", "Jaderholm, E. (1909) Northern and Arctic invertebrates in the collection of the Swedish State Museum (Riksmuseum). IV. Hydroiden. Kungliga Svenska Vetenskapsakademiens Handlingar, ny foljd, 45 (1), 1 - 124.", "Jagerskiold, L. A. (1971) A survey of the marine benthonic macro-fauna along the Swedish west coast 1921 - 1938. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 6, 1 - 146.", "Cornelius, P. F. S. (1995 a) North-west European thecate hydroids and their medusae. Part 1. Introduction, Laodiceidae to Haleciidae. Synopses of the British Fauna, n. s., 50, 347 pp.", "Clark, S. F. (1875) Descriptions of new and rare species of hydroids from the New England coast. Transactions of the Connecticut Academy of Arts and Sciences, 3, 58 - 66.", "Calder, D. R. (1971) Hydroids and hydromedusae of southern Chesapeake Bay. Virginia Institute of Marine Science, Special Papers in Marine Science, 1, 1 - 125.", "Forbes, E. (1848) A monograph of the British naked-eyed medusae: with figures of all the species. Ray Society, London, 104 pp.", "Schuchert, P. (2001 b) Survey of the family Corynidae (Cnidaria, Hydrozoa). Revue Suisse de Zoologie, 108, 739 - 878.", "Kramp, P. L. (1935 b) Polypdyr (Coelenterata) I. Ferskvandspolypper og goplepolypper. Danmarks Fauna, 41, 1 - 207.", "Rees, W. J. & Rowe, M. (1969) Hydroids of the Swedish west coast. Acta Regiae Societatis Scientiarum et Litterarum Gothobergensis, Zoologica, 3: 1 - 23.", "Stechow, E. (1923) Zur Kenntnis der Hydroidenfauna des Mittelmeeres, Amerikas und anderer Gebiete. II. Teil. Zoologische Jahrbucher, Abteilung fur Systematik, Okologie und Geographie der Tiere, 47, 29 - 270.", "Christiansen, B. O. (1972) The hydroid fauna of the Oslo Fiord in Norway. Norwegian Journal of Zoology, 20, 279 - 310.", "Ronowicz, M. (2007) Benthic hydroids (Cnidaria: Hydrozoa) from Svalbard waters - biodiversity and distribution. Journal of the Marine Biological Association of the United Kingdom, 87, 1089 - 1094.", "Schuchert, P. (2001 a) Hydroids of Greenland and Iceland (Cnidaria, Hydrozoa). Meddelelser om Gronland, Bioscience, 53, 1 - 184.", "Calder, D. R. (1970) Thecate hydroids from the shelf waters of northern Canada. Journal of the Fisheries Research Board of Canada, 27, 1501 - 1547.", "Fraser, C. M. (1944) Hydroids of the Atlantic coast of North America. University of Toronto Press, Toronto, 451 pp."]}